P-086 Predictors of Affective Spectrum Disorders in Inflammatory Bowel Disease. (February 2017) - Navabi, Seyedehsan; Gorrepati, Venkata Subhash; Stern, Benjamin; Falaiye, Tolulope; Koltun, Walter; Deiling, Sue; Stuart, August; Tinsley, Andrew; Coates, Matthew; Williams, Emmanuelle
Abstract : Background: Previous studies have demonstrated that individuals with inflammatory bowel disease (IBD) are more likely to develop affective spectrum disorders (ASD), including anxiety and depression, when compared to their age-matched counterparts. Management of both ulcerative colitis (UC) and Crohn's disease (CD) is more challenging in the setting of ASD and is associated with increased burden on patient quality of life and healthcare costs. In order to improve our ability to care for IBD patients suffering with ASD, we need to have a better understanding for the underlying drivers of these disorders in this population. The aim of this study was to determine the clinical factors that influence development of anxiety and depression in IBD. Methods: We performed a retrospective analysis using a consented IBD natural history registry between January 1, 2015 and June 30, 2016 from a single tertiary care referral center. Presence of anxiety or depression was determined based upon responses to the Hospital Anxiety and Depression Scale (HADS) using a score of 8 or greater to indicate clinically significant presence of each. Age, gender, IBD duration, IBD extent, disease complications (including abscess and stricture development), extra intestinal manifestations (EIM), physician global assessment (PGA), endoscopic severity, Harvey Bradshaw Index, Simple Clinical Colitis Activity Index, medication use (including antidepressant, anxiolytic, corticosteroid, mesalamine, immunomodulator and biologic), surgical history, laboratory values (ESR, CRP, Vitamin D, Zinc), opiate and tobacco use (active and former) were also abstracted. Results: A total of 262 IBD patients (130f:132 m) were included in this study. Eighty-six had UC (32.8%; 40f:46 m), 163 had CD (62.2%, 83f:80 m) and 13 had indeterminate colitis (5.0%, 7f:6 m). One hundred twenty-one IBD patients (46.1%) were found to have clinically significant anxiety and/or depression scores. Significant disease (defined as moderate to severe activity with PGA and/or on endoscopic evaluation) was more common in patients with ASD (45.7% versus 24.3%, P < 0.001). Using multivariate analysis, younger age ( P < 0.05) and higher disease activity index ( P < 0.05) were both independently predictive of ASD. Immunomodulator use was less likely to be associated with ASD ( P < 0.05). Other factors, including presence of EIM ( P = 0.06), low vitamin D levels ( P = 0.014) and corticosteroid use ( P = 0.16) notably trended toward significance in this analysis. Similar trends were recapitulated in both the UC and CD subpopulations. Conclusions: This study demonstrated once again that anxiety and depression are very common in the setting of IBD, in both CD and UC. Significant predictors of these disorders in IBD were younger age and clinical indicators of more severe inflammation. Other factors associated with more severe disease burden (including presence of EIM, vitamin D deficiency and use of corticosteroid) may also be important but more study is required to verify their potential role in this regard. Of the therapies evaluated in this study, only immunomodulator use demonstrated a significant independent effect against the development of ASD. These findings help to refine our understanding of ASD development in IBD and provide potential strategies for ASD risk identification and management in this setting.